Marijuana Use Is Associated with Behavioral Approach and Depressive Symptoms in Adolescents and Emerging Adults - Wright, Natasha E. (PLoS One, 2016)
BACKGROUND: Repeated CB1 binding due to THC results in downregulation of the endocannabinoid system in cortex and limbic regions, perhaps disrupting frontolimbic functioning. This is particularly a concern in young adults who are still undergoing neurodevelopment in frontal and limbic regions. Such disruptions may be linked to increased depressive symptoms, anxiety symptoms, and executive dysfunction, and decreased behavioral approach. OBJECTIVES: Here we examine the influence of young adult marijuana use on anxiety, depressive symptoms, behavioral approach, and executive dysfunction. The influence of alcohol and gender were also assessed. METHODS: 84 participants (42 MJ, 42 controls) aged 18–25 were balanced for gender (39 F). Exclusion criteria included: MRI contraindications, left handed, comorbid Axis-I disorders, major medical or neurologic disorders, prenatal issues, or prenatal alcohol/illicit drug exposure, or excessive other drug use. Participants completed the FrsBE, BIS/BAS, State-Trait Anxiety Inventory (State), and BDI-II. Multiple regressions were run to predict anxiety, depressive symptoms, behavioral approach, and executive dysfunction from MJ group status, past year alcohol use, gender, and MJ*gender interactions, controlling for cotinine and ecstasy. RESULTS: MJ group predicted increased depressive symptoms (p =.049). Decreased fun-seeking (p =.04), reward response (p =.01), and BAS total (p =.01) were predicted by MJ group. Gender predicted decreased reward responsiveness in females (p =.049) and decreased BIS in females (p =.03). Female marijuana users had increased anxiety symptoms (p =.04) and increased disinhibition (p =.04). Increased cotinine predicted increased drive (p =.046), reward responsiveness (p =.008) and BAS Total (p =.02). Apathy and Executive Dysfunction were not predicted by any measures. All results had small effect sizes. CONCLUSIONS/IMPORTANCE: Depressive symptoms were greater in MJ users, while behavioral approach was decreased. Cotinine levels predicted increased behavioral approach. Female MJ users also had greater anxiety and disinhibition. In sum, these findings suggest sub-clinical threshold deficits related to regular marijuana use that are indicative of a need to prevent marijuana use in adolescents and young adults.